2022
DOI: 10.1055/s-0041-1740985
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation after Rheumatic Heart Valve Surgery: Incidence, Predictors, and Outcomes

Abstract: Background Atrial fibrillation after cardiac surgery (AFACS) impacts 10 to 65% of patients. AFACS is associated with stroke and other systemic embolic manifestations. Methods Patients at our hospital who underwent rheumatic valve surgery procedures including aortic valve replacement (AVR), mitral valve replacement (MVR), AVR with coronary artery bypass grafting (CABG), MVR with CABG, or AVR and MVR with/without CABG were included in this study in the period from 2002 to 2017. Results In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Following CABG, valve surgery is second in terms of frequency of performance as open-heart surgery in Jordan. Our studies results regarding mortality and morbidity after valve operations have been published previously (5)(6)(7). According to these studies, age, emergency valve surgery, EF<35%, use of beta-blockers for more than a month before surgery, use of a tissue valve, type of surgery performed, pump run time, and cross-clamp time were all found to be independent predictors of mortality after valve heart surgery.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Following CABG, valve surgery is second in terms of frequency of performance as open-heart surgery in Jordan. Our studies results regarding mortality and morbidity after valve operations have been published previously (5)(6)(7). According to these studies, age, emergency valve surgery, EF<35%, use of beta-blockers for more than a month before surgery, use of a tissue valve, type of surgery performed, pump run time, and cross-clamp time were all found to be independent predictors of mortality after valve heart surgery.…”
Section: Discussionmentioning
confidence: 52%
“…In a previous study on the same cohort, we showed that LA enlargement was associated with postoperative atrial fibrillation. 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations